Head‐to‐head comparison of two transcription‐mediated amplification assay versions for detection of hepatitis B virus, hepatitis C virus, and human immunodeficiency virus Type 1 in blood donors. Issue 10 (17th April 2013) - Grabarczyk, Piotr; van Drimmelen, Harry; Kopacz, Aneta; Gdowska, Jolanta; Liszewski, Grzegorz; Piotrowski, Dariusz; Górska, Joanna; Kuśmierczyk, Jolanta; Candotti, Daniel; Łętowska, Magdalena; Lelie, Nico; Brojer, Ewa
Abstract : Background: The second triplex transcription‐mediated amplification (TMA) assay version (Ultrio Plus, Novartis Diagnostics) uses an additional reagent enhancing the disruption of hepatitis B virus (HBV) particles and release of DNA for the target capture probe. This study compares the performance of this new assay version with the previous one (Ultrio). Study Design and Methods: For analytical sensitivity assessment the World Health Organization HBV, hepatitis C virus (HCV), and human immunodeficiency virus (HIV) international standards and various genotype dilution panels were used. Individual donations (IDs) from 9980 first‐time donors were screened simultaneously by serology and both TMA assay versions. Results: The 50 and 95% limits of detection (LODs) for HBV using Ultrio Plus were 0.8 (0.6‐1.0) and 4.6 (3.2‐7.2) IU/mL, respectively, 2.4 (1.4‐4.8)‐fold more sensitive than Ultrio. The TMA assay versions had comparable LODs for HIV‐1 and HCV. The improvement factors on analytical sensitivity panels of HBV Genotypes A to G ranged from 1.3 to 7.3 and 50% LODs (95% confidence interval) reduced from 12.5 (10‐15) to 3.8 (3.2‐4.4) copies/mL. One Ultrio Plus HBV Genotype D yield sample missed by the Ultrio assay in the donor screening study was detected with ninefold higher sensitivity. The specificities of ID nucleic acid test (ID‐NAT) and serologic testing in a similar repeat test algorithm were 100 and 99.41%, respectively. Conclusion: More efficient target capture chemistry in the new TMA assay version significantly improved sensitivity and diminished variability in detecting HBV strains of various genotypes. We recommend a triplicate ID‐NAT repeat test strategy to eliminate discriminatory tests on false‐non–repeat‐reactive (anti‐HBc–nonreactive) donations.